KINERJA EFISIENSI KANTOR PELAYANAN PAJAK PRATAMA: PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - Hendra Triantoro; Bambang Subroto (Universitas Negeri Malang, 2017)
This research aims to assess the technical efficiency performance of Small Taxpayer Office (KPP Pratama) in the Regional Tax Office of East Java III, during 2011-2014, uses Data Envelopment Analysis (DEA) approach. Input variables are spending, the number of Account Representative, and the number Tax Auditor, while tax revenues are selected as output variable. The results showed that there were four units Small Taxpayer Office, that are more efficient compared to other units. Reallocation of input resources are needed to improve the efficiency pf the other units.Keywords: efficiency, Data Envelopment Analysis (DEA), Small Taxpayer Office